Sertula florae colombiae, X: Nuevas especies de Miconia (Melastomataceae) - Uribe Uribe Lorenzo (Caldasia)
Miconia laetervirens, L. Uribe, sp. nov. / Miconia orescia L. Uribe, sp. nov. / Miconia sciurea L. Uribe, sp. nov.